2015
DOI: 10.1074/jbc.m114.611483
|View full text |Cite
|
Sign up to set email alerts
|

Prolyl-4-hydroxylase Domain Protein 2 Controls NF-κB/p65 Transactivation and Enhances the Catabolic Effects of Inflammatory Cytokines on Cells of the Nucleus Pulposus

Abstract: Background:The regulatory mechanism of PHD2 function and expression under inflammatory conditions in the nucleus pulposus is unknown. Results: PHD2 controls TNF-␣ effects by positively regulating NF-B signaling, whereas NF-B mediates cytokine-dependent PHD2 expression. Conclusion: PHD2 and NF-B forms a functional circuit that promotes the catabolic effects of TNF-␣ in the intervertebral disc. Significance: PHD2 may play an important role in pathogenesis of disc disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
44
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
9
1

Relationship

3
7

Authors

Journals

citations
Cited by 52 publications
(47 citation statements)
references
References 43 publications
3
44
0
Order By: Relevance
“…Importantly, TLR2 activation provides another mechanism for activating p38, ERK1/2, and NF-B signaling during disc degeneration. Furthermore, phosphorylation of NF-B is sustained (Ͼ30 min), which agrees with other studies that have found prolonged NF-B activation in NP and AF cells (46,47). For other pathologies, both p38 (rheumatoid arthritis) and NF-B (atopic dermatitis) inhibitors have gone to clinical trials (45).…”
Section: Tlr2 Regulates Ngf Via Nf-bsupporting
confidence: 78%
“…Importantly, TLR2 activation provides another mechanism for activating p38, ERK1/2, and NF-B signaling during disc degeneration. Furthermore, phosphorylation of NF-B is sustained (Ͼ30 min), which agrees with other studies that have found prolonged NF-B activation in NP and AF cells (46,47). For other pathologies, both p38 (rheumatoid arthritis) and NF-B (atopic dermatitis) inhibitors have gone to clinical trials (45).…”
Section: Tlr2 Regulates Ngf Via Nf-bsupporting
confidence: 78%
“…Conversely, another group has found that PHD3 inhibits NF-κB by a prolyl hydroxylase-independent inhibition of IKKγ ubiquitination [92]. In addition, a cooperative role of PHD2 with respect to NF-κB activity, functioning as coactivator of p65, has been shown [94]. Taken together, these studies exemplify the cell type and context specificity of hypoxia induced NF-κB regulation by PHDs.…”
Section: Role Of the Oxygen Sensors In The Hypoxia Induction Of Nf-κbsupporting
confidence: 49%
“…Li et al [73] found that prolyl hydroxylase (PHD) 2 functions as a co-activator of NF-κB p65 to promote matrix catabolism induced by TNF-α. Exposure of NP cells to TNF-α up-regulates the expression of PHD2, which then interacts with NF-κB p65 to stimulate the transcription of MMP-3, MMP-13, and ADAMTS-5 [73]. Similar to PHD2, PHD3 plays a significant role in promoting TNF-α-induced activation of NF-κB and subsequent synthesis of ADAMTS-5 and MMP-13 [74].…”
Section: Tnf-α Promotes Ecm Degradationmentioning
confidence: 99%